Children's art creations with the theme of parents' professions in Ngepungrojo Village, Pati - Sri Bintang Kusmawati; Nur Fajrie; Imaniar Purbasari (Kepompong Children Centre Journal, 2023)
This study aims to determine the process of work carried out by children to draw an idea, the creative power of children in sketching and coloring, as well as the evaluation system for drawing exercises for children by providing input, directions, and assessments in the form of interpreting social values ​​from the livelihoods of their parents in the Ngepungrojo village City of Pati. The research approach uses a narrative research method based on Creswell's theory: 2019. Data collection techniques are through interviews, observation, and documentation. then the Milles and Huberman data analysis used by the author in this study. The results of the discussion show that each child has different perceptions and experiences as well as in the process of creating images that differ in the meaning of the results of the images.